Analisis Faktor-Faktor Yang Mempengaruhi Pertumbuhan Produk Domestik Bruto Di Asia Menggunakan Model Regresi Dummy - Ivanna Genardi, Angelina; Rahkmawati, Yeni; Muhajirin Farid, Fuad (Program Studi Statistika Fakultas MIPA UNM, 2025)
This study aims to analyze the factors influencing the Gross Domestic Product (GDP) of 45 Asian countries in 2021. Understanding these factors is crucial for formulating effective development policies and achieving the Sustainable Development Goals (SDGs). Data were sourced from Our World in Data and the World Bank. Dummy regression was employed to examine the effects of the Human Development Index (HDI), population size, and income classification on GDP. The results indicate that HDI and income classification significantly impact GDP, while population size does not. High-income countries have higher GDP compared to others. The regression model achieved an Adjusted R-Square value of 0.9058, explaining 90.58% of the variability in GDP. These findings highlight that enhancing human resource quality is essential for driving economic growth, particularly in low- and middle-income countries in Asia. This study offers valuable insights for policymakers in fostering sustainable development